Psychosocial predictors of problematic eating in young adults who underwent adolescent bariatric surgery. (22nd January 2022) - Decker, Kristina M.; Reiter‐Purtill, Jennifer; Bejarano, Carolina M.; Goldschmidt, Andrea B.; Mitchell, James E.; Jenkins, Todd M.; Helmrath, Michael; Inge, Thomas H.; Michalsky, Marc P.; Zeller, Meg H.
Abstract: Introduction: This study examined problematic eating and eating‐related psychopathology among young adults who underwent adolescent bariatric surgery including concurrent and prospective associations with psychosocial factors and weight change. Methods: VIEW point is a 6‐year follow‐up study within a prospective observational study series observing adolescents with severe obesity who had bariatric surgery ( n = 139) or who presented to nonsurgical lifestyle modification programs ( n = 83). Participants completed height/weight measurements, questionnaires, and diagnostic interviews. Regression analyses compared problematic eating across groups and examined Year 6 correlates (i.e., psychosocial factors and weight change) and baseline predictors (i.e., psychosocial factors) of eating‐related psychopathology. Results: Compared to the nonsurgical group, the surgical group reported lower eating‐related psychopathology, objective binge eating, and grazing at Year 6. While chewing/spitting out and vomiting for weight/shape‐related reasons were very infrequent for the surgical group, self‐induced vomiting for other reasons (e.g., avoid plugging) was more common. For the surgical group, lower self‐worth, greater internalizing symptoms, and higher weight‐related teasing in adolescence predicted increased eating‐related psychopathology in young adulthood. Year 6 eating‐related psychopathology was concurrently associated with lower percent weight loss for the surgical group and greater percent weight gain for the nonsurgical group. Conclusion: Undergoing adolescent bariatric surgery appears to afford benefit for problematic eating and eating‐related psychopathology. Current findings suggest that the clinical intervention related to problematic eating and associated psychosocial concerns may be needed for young adults with obesity, regardless of surgical status.